2022
DOI: 10.1038/s41528-022-00138-y
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the superior thermoelectric property of post-treatment-free PEDOT:PSS/IL hybrid by X-ray and neutron scattering characterization

Abstract: In this work, a polymer and ionic liquid (IL) hybrid with superior thermoelectric performance is prepared via a system design of the chemical composition, molar ratio of the constituent molecules and manipulating the structure in solution and dried films. The solution-casted hybrid film, consisting of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and 1-ethyl-3-methylimidazolium tricyanomethanide (EMIM:TCM), shows the highest power factor of 175 μW m−1 K−2 in the polymer hybrid prepared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…This suggests that the extra-Raman modes observed in samples treated in PBS 10× might be characteristic of PSS segregation or reflect the increased crystallization of the PEDOT chains during chain separation/segregation. This framework is consistent with the small-angle X-ray scattering (SAXS)- and small-angle neutron scattering (SANS)-based study on the interaction of ionic liquid electrolytes with PEDOT:PSS, recently reported by Li et al, which demonstrated that high ionic concentrations destabilize the interaction between the chains, leading to their excessive separation and segregation . In particular, this work showed a progressive transition from a core/shell to rodlike structures as a function of the electrolyte concentration.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the extra-Raman modes observed in samples treated in PBS 10× might be characteristic of PSS segregation or reflect the increased crystallization of the PEDOT chains during chain separation/segregation. This framework is consistent with the small-angle X-ray scattering (SAXS)- and small-angle neutron scattering (SANS)-based study on the interaction of ionic liquid electrolytes with PEDOT:PSS, recently reported by Li et al, which demonstrated that high ionic concentrations destabilize the interaction between the chains, leading to their excessive separation and segregation . In particular, this work showed a progressive transition from a core/shell to rodlike structures as a function of the electrolyte concentration.…”
Section: Resultssupporting
confidence: 92%
“…Partial separation between PEDOT and PSS chains was observed for the concentration of electrolyte around 0.09 M, whereas an increase of the concentration to 0.33 M results in excessive separation of the chains, which gives rise to phase segregation. 22,23…”
Section: Using Pedot:pss For Probing Redox Mediatorsmentioning
confidence: 99%
“…Partial separation between PEDOT and PSS chains was observed for concentration of electrolyte around 0.09 M, whereas an increase of concentration to 0.33 M results in excessive separation of the chains, which gives rise to phase segregation. 22,23 Raman Shift (cm Interestingly, the same effect was also observed by direct deposition of PEDOT:PSS thin films on different types of metallic substrates (Figure 4a). We note that PEDOT:PSS exhibit a Raman spectrum analogous to those observed in samples treated in PBS 10X solutions or electrically biased when deposited onto iron or zinc foils (or powders), whereas it remains almost unaltered in contact with gold.…”
Section: Hydrated Cationssupporting
confidence: 70%
“…This framework is consistent with the small angle X-ray (SAXS) and neutron (SANS) scattering-based study on the interaction of ionic liquid electrolytes with PEDOT:PSS, recently reported by Li et al, which demonstrated that high ionic concentrations destabilize the interaction between the chains, leading to their excessive separation and segregation. 22 In particular, this work showed a progressive transition from a core/shell to rod-like structures as a function of the electrolyte concentration.…”
Section: Hydrated Cationsmentioning
confidence: 71%
“…40 Later Kee et al reported that ionic liquids consisting of EMIM DCA or EMIM DCl can manipulate the doping level and nanostructure of PEDOT:PSS through ion exchange, which leads to a remarkable increase in the conductivity and Seebeck coefficient (up to 538 S cm À1 and 35 mV K À1 , respectively). 41 Similar contributions have been realized for PEDOT:PSS lms constructed by ionic liquid coatings based on BMIM or EMIM cations with various anions; [42][43][44][45][46][47][48][49][50][51][52][53] and their thermoelectric performances are summarized in Table S1. † The addition of or treatment with these ionic liquids in previous studies indicates the direction for manipulating the thermoelectric performance.…”
Section: Introductionmentioning
confidence: 65%